2017
DOI: 10.1186/s11671-017-2388-y
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on a Crystalline-Silicon Solar Cell with Black Silicon Layer at the Rear

Abstract: Crystalline-Si (c-Si) solar cell with black Si (b-Si) layer at the rear was studied in order to develop c-Si solar cell with sub-band gap photovoltaic response. The b-Si was made by chemical etching. The c-Si solar cell with b-Si at the rear was found to perform far better than that of similar structure but with no b-Si at the rear, with the efficiency being increased relatively by 27.7%. This finding was interesting as b-Si had a large specific surface area, which could cause high surface recombination and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…All the wafers with MACE show a slight decrease in minority carrier lifetime. It has been demonstrated that the minority carrier lifetime decreases by increasing the front surface area [26,27]. The MACE processes lead to dangling bonds and dislocations that also result in a severe Shockley–Read–Hall recombination [18].…”
Section: Resultsmentioning
confidence: 99%
“…All the wafers with MACE show a slight decrease in minority carrier lifetime. It has been demonstrated that the minority carrier lifetime decreases by increasing the front surface area [26,27]. The MACE processes lead to dangling bonds and dislocations that also result in a severe Shockley–Read–Hall recombination [18].…”
Section: Resultsmentioning
confidence: 99%
“…In the followings, for the numerical calculations, we use the parameters of halide PVK (CH 3 NH 3 PbI 3 ), TiO 2 as ETM and NiO as HTM. To construct the energy diagram, we used the following knowledge for the energy of the band gap (E g ), the affinity ( χ) and discontinuities in the conduction and valence bands (ΔE C , ΔE V ) of materials: [37] ; [38] 1 ; [39] ; ( [21] ); [40] ; [41] ; [37] ; [15] ; [39] ; [42] ; [40] ; ; ; ; ; ; ; ; Under the action of the incident radiation, multiple reflections occur inside the structure. For further theoretical modeling of such a three-layer structure, we represent each layer with its complex refractive index and corresponding thickness (Figure 2).…”
Section: Theory and Simulationmentioning
confidence: 99%
“…A simple empirical relationship between the band-gap energy and refractive index for PVK was developed and proposed. Due to the wider band gap of PVK (1.56-1.65 eV) than that of b-Si (1.54 eV [15] ) and c-Si (1.12 eV), its absorption spectrum is shifted to a short-wavelength region of the spectrum, where the absorption of b-Si and c-Si is lower.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Although the photoelectric conversion efficiency of the c-Si solar cell in the laboratory has been approaching its theoretical limit, [7][8][9] for commercial c-Si solar cells, there is still much room to improve their performances by further reducing optical and electrical losses and extending the wavelength range of photovoltaic response in costeffective manners. [10][11][12][13][14][15] The approach of hydrogen plasma passivation has usually been used to enhance the photocharge transport by passivating bulk dangling bonds in the a-Si, c-Si, and other solar cells. [16][17][18][19][20][21][22][23][24][25][26][27] However, approaches of this kind would bring severe ion-radiation damages to solar cells, which degrade the performance of a solar cell.…”
Section: Introductionmentioning
confidence: 99%